PENGARUH PIJAT PERINEUM TERHADAP ROBEKAN PERINEUM PADA IBU BERSALIN MULTIGRAVIDA DI BPM S DAN BPM E BINTARA JAYA TAHUN 2023 - Putri Febrianti, Cindy; Namirah Zasqiah Burhan, Dela (Journal of Midwifery Tiara Bunda, 2023)
Background: Perineal tears are injuries that often occur during the birth process. Perineal tears occur in almost all first deliveries and are not uncommon in subsequent deliveries. Perineal tears cause discomfort during the postpartum period and are even a cause of respiratory infections. Efforts to prevent perineal tears have been made, including perineal massage. Objective: To determine the relationship between perineal massage and perineal tears in multigravida mothers Method: The type of research used is a one group design posttest only approach. This study used term multigravida pregnant women (37 weeks to 40 weeks pregnant) with birth estimates during July - August 2024 whose previous births took place at BPM S and BPM E Bintara Jaya and had a history of perineal tears in previous births. Meanwhile, to find out perineal tears after the mother gives birth or when the mother gives birth by looking at the partograph monitoring tool. Results: Based on the results of the t test analysis on perineal massage data on perineal tears in women giving birth, the p value (0.000) <0.05 was obtained, these results indicate that there is a relationship between perineal massage and perineal tears in women giving birth. Conclusion: There is a relationship between perineal massage and perineal tears in multigravida mothers